Pengaruh Komposisi Media Baglog terhadap Pertumbuhan Jamur Kuping (Auricularia auricula) - Nanang Wahyu Prajaka; Yeni Yeni; Fahri Ali; Rahayu Opi Anggoro (JURNAL PERTANIAN, 2026)
Wood ear mushroom is one of the edible mushrooms that are in great demand by the community and widely consumed in Indonesia. Wood ear mushroom cultivation has been inefficient; however, it has economic and nutritional value. Wood ear mushrooms naturally grow on woody media containing cellulose and hemicellulose. The aim of this study was to determine the potential of bamboo waste as a growing medium for the growth and yield of wood ear mushrooms. This research was conducted using Randomized Block Design (RBD) with one factor and five replicates. The treatments used are different baglog media compositions: B1: 100% sawdust waste; B2: 100% bamboo waste; B3: 75% bamboo waste + 25% sawdust waste; B4: 50% bamboo waste + 50% sawdust waste; B5: 25% bamboo waste + 75% sawdust waste. Each experimental unit consisted of 10 baglogs. Data were analyzed using analysis of variance and 5% of the Tukey HSD test. This study provides the following result: mycelium filled the baglog at 70 days after inoculation (DAI), B1 and B5 had the fastest time of mycelium growth and filled the baglog at 42 DAI. The fastest primordia appearance times were at B1 and B5 at 51 DAI and 52 DAI. The optimal treatment overall is the B5 treatment, indicating that bamboo waste can only replace 25% of the whole mixed media with sawdust